Depth of bedrock in the Seal Cove river valley, Newfoundland: a geophysical case study - Schillereff, E.; Miller, Hugh; Gale, John (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1987)
Depth to bedrock was determined over part of the Precambrian Holyrood granite in the Seal Cove River valley, Avalon Peninsula, Newfoundland, using both electromagnetic and refraction hammer seismic methods. These geophysical interpretations, based on an assumed two-layer geometry, were compared with direct probe and drilling records of depth to bedrock. Combined data show that the cover sequence (glacial drift and peat bog) ranges from zero to eight meters in thickness, and overlies subhorizontal glaciated granite. The buried granite surface dips gently northwards, down valley, and Includes isolated humtnocka and hollows, which are interpreted to be buried roche mountonnee and ice-plucked depressions. Granite resistivity and congressional wave velocity minima coincide, and are thought to indicate areas of dense meaoscopic fracturing in the granite. Seismic depths are within 0.2 m of true depth where thicknesses are less than one meter, and are generally accurate to 101 elsewhere. EM depths are subject to uncertainties of u[j[»er layer resistivity values, and problems caused by power line interference, but. by cross-calibration with other methods, are within 0-28 m of true depth In the one meter range, even In saturated peat bog, and within 0.86 m where thicknesses are approximately seven meters.